La perception des élèves à l’égard de l’application des variations de brise-glace sur le sujet français dans la classe XI à SMA Negeri 8 Semarang - Hanifa Siti Azzahrah; Dwi Astuti (Universitas Negeri Semarang, 2024)
Ice breaking in a learning process is an activity in the form of a game carried out to break the atmosphere and physical rigidity and refocus the attention of students. The purpose of this study is to describe students’ perceptions toward the application of ice-breaking variations on French subjects in class XI at SMA Negeri 8 Semarang. This study used a quantitative descriptive approach. The sample of this study was 35 students from class XI Social Three at SMA Negeri 8 Semarang. Data was collected through questionnaires, with a total of 42 questions compiled based on seven indicators. The results showed that students’ perceptions toward the application of ice-breaking variations on French subjects in class XI at SMA Negeri 8 Semarang received a score of 4,567 and were included in the good criteria. This means that students positively accept the application of ice-breaking activities in the classroom learning process.